Factors contributing to success and failure in knowledge transfer in agriculture : a grounded theory study among paddy farmers in Selangor, Malaysia / Dang Merduwati Hashim - Hashim, Dang Merduwati (2008)
The main objective of ' this study is to understand, identify and describe the factors contributing to success in knowledge transfer from agricultural research findings to the farmers. Ultimatel y , this study is aimed at generating a theory of knowledge transfer within a substantive setting by employing Glaser's principles of grounded theory. Twelve farmers and I'Mir of their family members from Kuala Selangor participated in the study. A qualitative approach using Glaser and Strauss' (1967) grounded theory methodology has been chosen due to the 'fit' qualities of the methodology, the qualities of the researcher and the realit y of constraints in collecting data from the participants. The ethics in qualitative research and fieldwork is applied in the conduct of the study.The research process. depicting the journey in generating the grounded theory and the content of emergent theory are presented in the form of' theoretical memos.